Effect of Aluminium Content in Aluminium Pillared Montmorillonite on Its Surface Acidity Properties - Is Fatimah; Narsito Narsito; Karna Wijaya (Institute for Research and Community Services (LPPM) ITB, 2011)
Aluminium pillared montmorillonites from Indonesian natural montmorillonite has been prepared using Al13 Keggin ion pillaring precursor in varied concentrations. Herein we studied their characterization and catalysis application for esterification reaction. X-ray diffraction (XRD), energy dispersive x-ray analysis (EDX), and BET gas sorption analysis were employed to characterize the prepared materials besides the characterization on surface acidity by pyridine and n-butylammine adsorptions and FTIR analysis. The result showed that significant improvement on physicochemical character data was obtained by a pillarization process. Such a process also provided improvements on catalytic activities in esterification reactions. The effect of aluminium content on material characters was discussed in this paper. It was observed from the catalytic activity tests that pillared montmorillonite samples demonstrated higher activity in esterification reaction relative to the raw montmorillonite. It was found that surface profile of materials consist of specific surface area, pore volume and Lewis acidity were significantly affect the catalyst activity.